Membangun Citra Internasional Jepang: Strategi Bahasa Diplomatik Pidato Fumio Kishida di Konferensi Jepang-Ukraina untuk Promosi Pertumbuhan Ekonomi dan Rekonstruksi - Oktaviani, Nurillah Rizqi; Nursidah, Nursidah (Vocational College of Diponegoro University, 2025)
This study examines Japan's diplomatic language strategies through Prime Minister Fumio Kishida's speech at the Japan-Ukraine Conference for Promotion of Economic Growth and Reconstruction. Using Norman Fairclough's Critical Discourse Analysis (CDA), the research investigates how diplomatic language tools like politeness, modality, and metaphors construct Japan's international image as a committed and peace-oriented nation. The study focuses on three dimensions: text, discursive practices, and social practices, to analyze linguistic elements and their broader socio-political contexts. The findings highlight that Kishida employs specific linguistic choices to convey Japan's solidarity and support for Ukraine amidst geopolitical challenges. Through the use of modality, Kishida reinforces Japan's authoritative yet empathetic stance, framing its support as both a moral and strategic obligation. Politeness strategies are used to establish rapport and mitigate potential tensions, while metaphors such as